Comprometimento e entrincheiramento organizacional como variáveis preditoras do impacto do treinamento no trabalho: um estudo de caso em uma instituição pública de ensino superior - Balsan, Laércio André Gassen (2011)
This work was developed with the aim to investigate the influence of organizational commitment and entrenchment, as well as the perceptions of servers at UFSM about organizational support for transfer of training on impact of training on the job. To this end, we carried out a descriptive explicative study, drawing on quantitative methodologies. The search sample consisted of 392 civil servents of a Federal Institution of Higher Education, to which a questionnaire was developed from a model of self-assessment of Training at Work of Abbad (1999) and model assessment of Commitment Organizational Entrenchment proposed by Bastos et al (2008). The data were analyzed using the software Excel, SPSS and SAS. Did basic descriptive statistics, correlation and application of regression models. We have identified positive correlations between dimensions of commitment and positive correlations between the dimensions of entrenchment. Were also found positive correlations between the impact of training on the job, support the transfer and affective commitment. The most interesting were a negative correlations demonstrated between impact and the dimensions of entrenchment: Limitations of alternatives and bureaucratic arrangements. Yet, regression analysis revealed that the model with higher predictive power of the impact of training on work explained its variance by 25% by the variables: Support to training transfer, Affective and entrenchment dimensions: bureaucratic arrangements (this was correlated negative). Still, the predictive strength of support for the transfer of training on the affective commitment was statistically modest, with only 10% of variance explained. Based on these results, we can draw some strategic suggestions for strengthening the impact and that the employee develops ties with the organization. In this sense, organizations could look to the fact that support the transfer of training and affective commitment constitute predictors of impact. Therefore, it is interesting that organizations become aware of its members to provide a work environment characterized by support in the search for improvement, as well as for its employees to be able to transfer new knowledge to the work section. This support will make individuals feel more committed emotionally.